The decomposition method for one dimensional biharmonic equations. (13th February 2006) - Khalifa, A.K.
This paper deals with the study of the numerical solution of biharmonic equations in one dimension. Biharmonic equations appear frequently in many areas of engineering and physics representing some phenomena. The solution of such problems has been tackled by many authors. In this paper, a numerical method based on the Adomian decomposition method is introduced for the approximate solution of the equations. The obtained results are presented where only a few terms are required to obtain a good approximation to the solution. This shows that the method is accurate and efficient.